Osteoskeletal Manifestations of Scurvy: MRI and Ultrasound Findings - Polat, A.V.; Bekci, T.; Say, F.; Bolukbas, E.; Selçuk, M.B. (Springer Verlag service@springer.de, 2015)
Scurvy has become very rare in the modern world. The incidence of scurvy in the pediatric population is extremely low. In the pediatric population, musculoskeletal manifestations are more common and multiple subperiosteal hematomas are an important indicator for the diagnosis of scurvy. Although magnetic resonance imaging findings of scurvy are well described in the literature, to our knowledge, ultrasound findings have not yet been described. In this article, we report a case of scurvy with associated magnetic resonance imaging and ultrasound findings. © 2015, ISS.
Keywords: Magnetic Resonance Imaging; Scurvy; Ultrasound